Model Pengukuran Kinerja dan Efisiensi Sektor Publik Metode Free Disposable Hull (FDH) - Akhmad Syakir Kurnia (Economic Journal of Emerging Markets, 2006)
Improved efficiency is the main effect expected from fiscal decentralization. Im¬proved efficiency could be gained on the presumptions that local governments are much better in identifying and fulfilling the needs of households, since they are closer to them, and in mobilizing and using local resources to pay for goods and services having purely local impacts. Once, improved efficiency could be gained, public sector performance increases.I developed a model to measure public sector efficiency (PSE) and public sector performance (PSP). I compute public sector performance (PSP) and Public Sector Effo¬ciency (PSE) indicators comprising a composite and five sub-indicators for Regen¬cy/municipolity in Central Java Province. The first two indicators reflects socio-economic indicators that take into account education and health outcomes. Three other indicators re¬flect the standard “musgravian” task for government: allocation, distribution and stabilisa¬tion. Keywords:    Fiscal Decentralization, Public Sector Efficiency (PSE), Public Sector Perform¬ance (PSP), Free Disposable Hull (FDH).